Factors Associated with the Need for Insulin as a Complementary Treatment to Metformin in Gestational Diabetes Mellitus - Matheus Leite Ramos de Souza; Rodrigo Ribeiro e Silva; Thiago Ribeiro e Silva; Larissa Cano de Oliveira; Guilherme Dienstmann; Iramar Baptistella do Nascimento; Jean Carl Silva (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2020)
Abstract Objective To evaluate the factors associated with the need for insulin as a complementary treatment to metformin in pregnant women with gestational diabetes mellitus (GDM). Methods A case-control study was performed from April 2011 to February 2016 with pregnant women with GDM who needed complementary treatments besides diet and physical exercise. Those treated with metformin were compared with those who, in addition to metformin, also needed the combination with insulin. Maternal characteristics and glycemic control were evaluated. Multinomial logistic regression models were developed to evaluate the influence of different therapies on neonatal outcomes. Results A total of 475 pregnant women who needed pharmacological therapy were evaluated. Of these, 366 (77.05%) were submitted to single therapy with metformin, and 109 (22.94%) needed insulin as a complementary treatment. In the analysis of the odds ratio (OR), fasting glucose (FG)<90 mg/dL reduced the odds of needing the combination (OR: 0.438 [0.235-0.815]; p=0.009], as well as primiparity (OR: 0.280 [0.111-0.704]; p=0.007]. In obese pregnant women, an increased chance of needing the combination was observed (OR: 2,072 [1,063-4,039]; p=0,032). Conclusion Obesity resulted in an increased chance of the mother needing insulin as a complementary treatment to metformin, while FG<90 mg/dL and primiparity were protective factors.